2014
DOI: 10.11646/phytotaxa.9.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Moss diversity: A molecular phylogenetic analysis of genera

Abstract: In this study we present phylogenetic and molecular phylogenetic diversity analyses of moss taxa from a total of 655 genera of mosses. Three loci were sampled: chloroplast ribosomal small protein 4, the intronic region of the mitochondrial NADH dehydogenase subunit 5, and partial sequences of the nuclear 26S ribosomal RNA. Maximum likelihood and Bayesian phylogenetic analyses were performed on individual loci and on multilocus data sets. A measure of phylogenetic diversity was calculated and constrasted among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
178
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(209 citation statements)
references
References 65 publications
25
178
0
6
Order By: Relevance
“…In line with earlier phylogenetic studies (Cox et al 2010;Fedosov et al 2015Fedosov et al , 2016Hedderson et al 2004;La Farge et al 2000, 2002Stech 2004;Tsubota et al 2003Tsubota et al , 2004, the analyses of the present dataset resolved three well-supported lineages within the Leucobryaceae: the dicranoid Campylopus clade, the dicranoid Dicranodontium clade and the leucobryoid clade. The latter is characterized by the leucobryoid costa as synapomorphic character (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with earlier phylogenetic studies (Cox et al 2010;Fedosov et al 2015Fedosov et al , 2016Hedderson et al 2004;La Farge et al 2000, 2002Stech 2004;Tsubota et al 2003Tsubota et al , 2004, the analyses of the present dataset resolved three well-supported lineages within the Leucobryaceae: the dicranoid Campylopus clade, the dicranoid Dicranodontium clade and the leucobryoid clade. The latter is characterized by the leucobryoid costa as synapomorphic character (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Bonfim Santos and Stech 2017) were not closely related to those in the Leucobryaceae, as proposed by Fleischer (1904), was confirmed by molecular data (e.g., Bonfim Santos and Stech 2017;Cox et al 2010;Fisher et al 2007;La Farge et al 2000). In contrast, molecular phylogenetic evidence suggested that a number of the Dicranaceae genera belong to the Leucobryaceae (Hedderson et al 2004;La Farge et al 2000, 2002Stech 1999Stech , 2004Tsubota et al 2003Tsubota et al , 2004.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Drummondia sinensis (accession numbers, FJ883993, FJ572610, FJ572456), Trichostomum tenuirostre (FJ884001, FJ572590, FJ572457), and Orthodicranum montanum (FJ572644, FJ883997, FJ572644, FJ572464) were used as outgroups based on large-scale phylogenetic analyses of mosses (Cox et al, 2010).…”
Section: Taxon and Molecular Samplingmentioning
confidence: 99%